Discovery of an unusually high number of de novo mutations in sperm of older men using duplex sequencing - Salazar, Renato; Arbeithuber, Barbara; Ivankovic, Maja; Heinzl, Monika; Moura, Sofia; Hartl, Ingrid; Mair, Theresa; Lahnsteiner, Angelika; Ebner, Thomas; Shebl, Omar; Pröll, Johannes; Tiemann-Boege, Irene (Genome Research, 2022)
De novo mutations (DNMs) are important players in heritable diseases and evolution. Of particular interest are highly recurrent DNMs associated with congenital disorders that have been described as selfish mutations expanding in the male germline, thus becoming more frequent with age. Here, we have adapted duplex sequencing (DS), an ultradeep sequencing method that renders sequence information on both DNA strands; thus, one mutation can be reliably called in millions of sequenced bases. With DS, we examined ∼4.5 kb of the FGFR3 coding region in sperm DNA from older and younger donors. We identified sites with variant allele frequencies (VAFs) of 10−4 to 10−5, with an overall mutation frequency of the region of ∼6 × 10−7. Some of the substitutions are recurrent and are found at a higher VAF in older donors than in younger ones or are found exclusively in older donors. Also, older donors harbor more mutations associated with congenital disorders. Other mutations are present in both age groups, suggesting that these might result from a different mechanism (e.g., postzygotic mosaicism). We also observe that independent of age, the frequency and deleteriousness of the mutational spectra are more similar to COSMIC than to gnomAD variants. Our approach is an important strategy to identify mutations that could be associated with a gain of function of the receptor tyrosine kinase activity, with unexplored consequences in a society with delayed fatherhood.